The Effect of Marketing Agility to Marketing Performance through Innovation Capability of Retail Company of Spare Parts for Heavy Equipment Coal Mining in East Kalimantan - Mawardi Sukardi; Saida Zainurossalamia ZA; Syarifah Hudayah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The high fluctuation of the coal market during the current Covid-19 pandemic has an impact on coal mining companies. Thus, making coal mining operational support companies, namely retail companies of heavy equipment spare parts for coal mining located in East Kalimantan, also in a state of uncertainty and must be able to adapt to the increasingly dynamic coal market conditions. To improve its marketing performance in these dynamic conditions to be sustainable, the company must be agile in its marketing and must have good, fast, and responsive innovation capabilities. So, this research was conducted to prove that there is an influence of marketing agility with marketing performance in the dynamic coal market conditions through the company's innovation capabilities. The population in this study are marketing practitioners, marketing managers, marketing directors and decision makers in retail companies of heavy equipment spare parts for coal mining in East Kalimantan, with sample of 100. This study uses descriptive analysis to determine the characteristics of the respondents' responses with purposive sampling method which aims to determine several criteria for the sample of respondents to employees. In the analysis of data processing, the structural equation modelling–partial least square (SEM-PLS) program was used to predict the model relationship between the variables and indicators studied. The results of this study indicate that marketing agility has a significant positive effect on innovation capability; innovation capability has a significant positive effect on marketing performance; Marketing agility has a positive significant effect on marketing performance and marketing agility has a significant positive effect on marketing performance through innovation capability.